2008
DOI: 10.1021/bi7014597
|View full text |Cite
|
Sign up to set email alerts
|

Single Mutation on the Surface of Staphylococcus aureus Sortase A Can Disrupt Its Dimerization

Abstract: Staphylococcus aureus Sortase A (SrtA) is an important Gram-positive membrane enzyme which catalyzes the anchoring of many cell surface proteins conserved with the LPXTG sequence. Recently SrtA has been demonstrated to be a dimer with a Kd of 55 microM in vitro. Herein, we show that a single point mutation of amino acid residue on the surface of SrtA can completely disrupt the dimerization. Native polyacrylamide gel electrophoresis and analytical gel filtration chromatography were used to detect the dimer-mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…The lack of copious cross-linking at residue K206 indicates the absence of nucleophiles that are in the close proximity to this residue and available to react with l -DOPA moiety. The yields of cross-linked dimer from K137DOPA (Figure 3, lane 3) and K206DOPA (Figure 3, lane 6) are consistent with the results from the point-mutation studies[12] (Figures S1 and S2). The data presented here are the first direct evidence to confirm the physical interaction of SrtA at the residue level.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The lack of copious cross-linking at residue K206 indicates the absence of nucleophiles that are in the close proximity to this residue and available to react with l -DOPA moiety. The yields of cross-linked dimer from K137DOPA (Figure 3, lane 3) and K206DOPA (Figure 3, lane 6) are consistent with the results from the point-mutation studies[12] (Figures S1 and S2). The data presented here are the first direct evidence to confirm the physical interaction of SrtA at the residue level.…”
supporting
confidence: 85%
“…Successful cross-linking supports our recent discovery of SrtA ΔN59 dimerization. [10,12] Furthermore, we have shown that the efficiency of the cross-linking does not cost its selectivity. The information from serial cross-linking experiments at different residues using the same method would allow us to fairly accurately map the dimerization domain of SrtA.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…S3, line 4). The formation of SrtA dimer is resulted from a disulfide bridge of two active site Cys184 residues located in enzyme under denaturing conditions without adding reducing reagent 55 . The eluate was dialyzed and lyophilized to yield 407.2 μg of protein, which suggested that 91% of the SrtA was immobilized onto the IDA-nickel magnetic particles according to the amount of SrtA in 5 mL of supernatant (449.0 μg).…”
Section: Resultsmentioning
confidence: 99%
“…With new diseases and increasing resistance to existing drugs, there is need to discover and develop new innovating drugs with diminished side effects to combat bacteria infections (Cirzrt et al, 2005;Zhu et al, 2008). The use of herbs to treat diseases is almost universal among non industrialised societies (Brater and Daly, 2000).…”
Section: Introductionmentioning
confidence: 99%